2012
DOI: 10.1002/pen.23209
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior and mechanical strength of poly(butylene succinate‐co‐ethylene glycol)‐based nanocomposites using functionalized multiwalled carbon nanotubes

Abstract: Biodegradable poly(butylene succinate-co-ethylene glycol) (PBSG)/multiwalled carbon nanotube (MWCNT) nanocomposites were successfully prepared through physical blending and silication between PBSG and acyl aminopropyltriethoxysilane functionalized multiwalled carbon nanotube (MWCNT-APTES). Nuclear magnetic resonance (NMR) spectra observations revealed that the PBSG chains were covalently attached to the MWCNT-APTES by hydrolysis. PBSG/ MWCNT-APTES nanocomposites after hydrolysis showed excellent interfacial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…59 Hou et al , also showed relatively moderate increase (~132%) in mechanical stiffness of polyvinyl alcohol (PVA) due to addition of single-walled and multiwalled CNTs. 50 Other polymers such as poly(dimethylsiloxane) (PDMS) 55 , polypropylene (PP) 52 , poly(butylene succinate-co-ethylene glycol) (PBSG) 56 , poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) 57 also showed moderate increase in mechanical properties as shown in Figure 5d. The results reported here (PGS-CNTs) are quite unique as more than 500% modulus of polymeric networks can be enhanced by just the addition of 1% CNTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Hou et al , also showed relatively moderate increase (~132%) in mechanical stiffness of polyvinyl alcohol (PVA) due to addition of single-walled and multiwalled CNTs. 50 Other polymers such as poly(dimethylsiloxane) (PDMS) 55 , polypropylene (PP) 52 , poly(butylene succinate-co-ethylene glycol) (PBSG) 56 , poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) 57 also showed moderate increase in mechanical properties as shown in Figure 5d. The results reported here (PGS-CNTs) are quite unique as more than 500% modulus of polymeric networks can be enhanced by just the addition of 1% CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…In subsequent cycle the energy loss was constant for the network. (d) The increase in mechanical stiffness due to addition of CNTs to different polymeric matrix is summarized (PVA 50 , PLGA 51 , PP 52 , PLC 53 , PU 54 , PDMS 55 , PBSG 56 , PHBV 57 , PI 58 , PE 59 , Morthane 60 ). These data has been re-plotted from published reports.…”
Section: Figurementioning
confidence: 99%
“…Carbon nanotubers (CNTs), owing to their remarkable electrical and mechanical properties, have been extensively investigated, for instance, to be dispersed into insulating polymeric matrices to improve electrical conductivities for applications as strain sensors, transparent electrodes, large-area flexible electronics, etc. [12][13][14][15]. As reported, the tensile strength of single-walled nanotubes (SWNTs) could be up to (0.32-1.47 TPa) [16] and the electrical conductivity range from 2 to 17 3 10 7 S m 21 [17], comparing with 6.30 3 10 7 S m 21 for silver-the best metal electric conductor.…”
Section: Introductionmentioning
confidence: 87%
“…Among the many available renewable polymer materials, poly(butylene succinate) (PBS) constitutes a natural alternative because of its biodegradable properties and good chemical and thermal resistances. Besides, PBS resins also present excellent processability [22,23].…”
Section: Introductionmentioning
confidence: 99%